FAKTOR-FAKTOR PENGHAMBAT PEMBANGUNAN RUMAH LAYAK HUNI UNTUK KAUM DHUAFA DI PROVINSI ACEH (STUDY KASUS: KABUPATEN ACEH UTARA) - Mustafaruddin Mustafaruddin; Mochammad Afifuddin; Abdul Munir (Prodi Magister Teknik Sipil Unsyiah, 2018)
The habitable home construction activity is the North Aceh Regency Government program dedicated to the Dhuafa people. The implementation of the project is submitted to the contractor as responsible for completing the construction of a habitable home. Each planned project must have an implementation plan, when the start and end of the project, on-site technical and resource provision is essential to avoid the risk of obstacles in the implementation of the project. Problems that arise in the field are very risky and should be avoided so that the project being done can run smoothly. The purpose of this research is to identify the factors of inhibition in the implementation of habitable home project for the Dhuafa as well as to analyze a good strategy in minimizing the inhibition. The research method used is mix methode between qualitative and quantitative method. The number of executors of Dhuafa house construction in 2016 is 64 companies. The number of respondents obtained from the slovin formula of 39 companies. The results of the research explain that the factors causing the occurrence of obstacles during the execution of work is the labor factor with the value of frequency index (FI) of 0,84; design and planning factors with an FI value of 0,81; factor of equipment with value of FI 0,77; factors beyond the contractor's ability with a FI value of 0,75; material factor with value of FI 0,55; field condition factor with FI value of 0,46; and implementation factor and working relationship with FI value of 0,40. The ways that can be done to avoid the occurrence of barriers in terms of labor is to improve the quality of labor, increase the workforce who are competent in their fields, and work in accordance with the procedure. In terms of design and planning is to do a design review of the project.